Protective effect of Aurelia aurita against free radicals and streptozotocin-induced diabetes - Mallikarjuna Rao Talluri; Alekhya Ketha; Ganga Rao Battu; Rajananda Swamy Tadi; Vinay Bharadwaj Tatipamula (Bangladesh Pharmacological Society, 2018)
The present work was carried out to identify the anti-oxidant and anti-diabetic activities of Aurelia aurita. The chemical profiling analysis showed that it possess different biologically active secondary metabolites like phenols, alakoids, steroids etc. The methanolic extract showed different free radical scavenging activity as ascorbic acid with  IC50 values 202, 205, 153 µg on DPPH, hydroxyl and superoxide free radicals. The extract significantly reduced the hyperglycemic conditions with percentage of reduction 18.7 ± 1.3 to 53.5 ±1.5 of streptozotocin-induced animals and the positive result of in-vitro aldose reductase enzyme inhibition with IC50 value 163 µg suggests that A. aurita have potential to cure the diabetic complications.